Tissue transglutaminase contributes to the pathogenesis of preeclampsia and stabilizes placental angiotensin receptor AT1 by ubiquitination-preventing isopeptide modification - Liu, Chen (2013)
Preeclampsia is a life-threatening pregnancy disorder that is widely believed to be triggered by impaired placental development. However, the placenta-related pathogenic factors are not fully identified and their underlying mechanisms in disease development remain unclear. Here we report that the protein level and enzyme activity of tissue transglutaminase (TG2 or tTG), the most ubiquitous member of a family of enzymes that conducts posttranslational modification of proteins by forming ε-(γ-glutamyl)-lysine isopeptide bonds, are significantly elevated in placentas of preeclamptic women. TG2 is localized in the placental syncytiotrophoblasts of preeclamptic patients where it catalyzes the isopeptide modification of the angiotensin receptor AT1. To determine the role of elevated TG2 in preeclampsia, we employed a mouse model of preeclampsia based on injection of angiotensin receptor type 1 agonistic autoantibody (AT1-AA). A pathogenic role for TG2 in preeclampsia is suggested by in vivo experiments in which cystamine, a potent transglutaminase inhibitor, or siRNA-mediated TG2 knockdown, significantly attenuated autoantibody-induced hypertension and proteinuria in pregnant mice. Cystamine treatment also prevented isopeptide modification of placental AT1 receptors in preeclamptic mice. Mechanistically, we revealed that AT1-AA stimulation enhances the interaction between AT1 receptor and TG2, and results in increased AT1 receptor stabilization via transglutaminase-mediated isopeptide modification in trophoblasts. Mutagenesis studies further demonstrated that TG2-mediated isopeptide modification of AT1 receptors prevents the ubiquitination-dependent receptor degradation. Taken together, our studies not only identify a novel pathogenic involvement of TG2 in preeclampsia but also suggest a previously unrecognized role of TG2 in the regulation of GPCR stabilization by inhibiting ubiquitination-dependent degradation.